C1 domain-targeted isophthalates as protein kinase C modulators: structure-based design, structure–activity relationships and biological activities. (17th November 2014) - Talman, Virpi; Provenzani, Riccardo; Boije af Gennäs, Gustav; Tuominen, Raimo K.; Yli-Kauhaluoma, Jari
Abstract : Protein kinase C (PKC) is a serine/threonine kinase belonging to the AGC family. PKC isoenzymes are activated by phospholipid-derived second messengers, transmit their signal by phosphorylating specific substrates and play a pivotal role in the regulation of various cell functions, including metabolism, growth, differentiation and apoptosis. Therefore they represent an interesting molecular target for the treatment of several diseases, such as cancer and Alzheimer's disease. Adopting a structure-based approach on the crystal structure of the PKCδ C1B domain, our team has developed isophthalic acid derivatives that are able to modify PKC functions by binding to the C1 domain of the enzyme. Bis[3-(trifluoromethyl)benzyl] 5-(hydroxymethyl)isophthalate (HMI-1a3) and bis(1-ethylpentyl) 5-(hydroxymethyl)isophthalate (HMI-1b11) were selected from a set of compounds for further studies due to their high affinity for the C1 domains of PKCα and PKCδ. HMI-1a3 showed marked antiproliferative activity in HeLa cells whereas HMI-1b11 induced differentiation and supported neurite growth in SH-SY5Y cells. Our aim in the future is to improve the selectivity and potency of isophthalate derivatives, to clarify their mechanism of action in the cellular environment and to assess their efficacy in cell-based and in vivo disease models. HMI-1a3 has already been selected for a further project and redesigned to function as a probe immobilized on an affinity chromatography column. It will be used to identify cellular target proteins from cell lysates, providing new insights into the mechanism of action of HMI-1a3.